A Comparative Study between Postextubation of Preterm Neonates into High-Flow Nasal Cannula versus Nasal Continuous Positive Airway Pressure - Ramy Morsy; Magda Sedky Badawy; Reem Said; Aliaa Ali; Walaa Abuelhamd (Mashhad University of Medical Sciences, 2021)
Background: For respiratory support in premature newborns, there has been a trend toward less trachealintubation, less mechanical ventilation, and more nasal respiratory support which can result in the improvement ofsuccessful extubation rate. The two commonly known types of nasal respiratory support after extubation are thenasal continuous positive airway pressure (CPAP) and high flow nasal cannula (HFNC). The current study aimed toinvestigate and compare successful extubation using HFNC and conventional nasal CPAP after a period ofendotracheal positive pressure ventilation and detect which of these two methods is better for successfulextubation with fewer side effects.Methods: This randomized controlled study was conducted on 210 preterm newborns in the neonatal intensive careunit (NICU) of Gynecology and Obstetrics Department of Qasr El Eyni Hospital. Post extubation failure rates werecompared between the two groups, namely (HFNC) and (nasal CPAP). The collected data were analyzed in SPSSsoftware (version 20).Results: Neonates who needed re-intubation within 72 h after initial extubation were higher in the HFNC group(72.7%) versus (27.3%) in the CPAP group (P-value=0.063). Moreover, 45.8% of neonates in the HFNC group neededre-intubation within 1 week of initial extubation versus 54.2% in CPAP (P-value=0.970). The mean duration ofrespiratory support using HFNC was 3.7 days, compared to 6.5 days using CPAP (P-value= 0.001). Among neonateswho suffered from nasal trauma, 90.6% of neonates belonged to the CPAP group, while 9.4% of cases belonged to theHFNC group (P-value= 0.001). Conclusion: The use of CPAP and HFNC after the extubation of preterm mechanically ventilated neonates wasstatistically equal regarding extubation failure.